2020
DOI: 10.1177/1097184x20901561
|View full text |Cite
|
Sign up to set email alerts
|

Are Men Who Pay for Sex Sexist? Masculinity and Client Attitudes Toward Gender Role Equality in Different Prostitution Markets

Abstract: Prostitution clients’ attitudes toward gender equality are important indicators of how masculinity relates to the demand for commercial sexual services. Research on male client misogyny has been inconclusive, and few studies compare men in different markets. Using an online survey of 519 clients of sexual services, we examine whether male client attitudes toward gender role equality are related to the main methods customers used to access prostitution services (i.e., through print or online media vs. in-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
2
6
0
2
Order By: Relevance
“…In line with previous research,4 13 18 19 the majority of participants reported that clients were non-predatory, non-violent, ‘average’ people. However, almost all acknowledged that, similar to other service industry work environments, they sometimes encounter clients who may be rude, coercive (ie, ask for services that were not offered), threatening, and in some cases, physically aggressive.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In line with previous research,4 13 18 19 the majority of participants reported that clients were non-predatory, non-violent, ‘average’ people. However, almost all acknowledged that, similar to other service industry work environments, they sometimes encounter clients who may be rude, coercive (ie, ask for services that were not offered), threatening, and in some cases, physically aggressive.…”
Section: Resultssupporting
confidence: 85%
“…While end-demand legislation is based on pervasive social representations of exploitative and predatory clients,14 our findings are consistent with past research4 11 13 17–20 37 38 demonstrating that client characteristics, demographics, attitudes and relationships are diverse, and tend to parallel those of the general public. Despite being a heterogeneous group, participants indicated that end-demand’s unilateral conceptualisation of clients as dangerous made it challenging for them to manage their work environments and intensified experiences of harm.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…El consumo de prostitución, pornografía o sexo de pago, responde mayoritariamente a una demanda masculina; son los hombres quiénes muestran las actitudes más favorables ante ella (Malamuth, 1996;Gomez-Suarez y Verdugo-Martés, 2015;Serrano, 2018). Estos hombres además manifiestan actitudes negativas hacia la igualdad de género, como un indicador de cómo esta masculinidad se relaciona con la demanda de servicios sexuales (Brents et al, 2020). Satz (2010) señala que la prostitución es "un teatro de desigualdad, nos muestra una práctica en la que las mujeres son vistas como sirvientas de los deseos de los hombres" (p.147).…”
Section: Introductionunclassified